2010
DOI: 10.1371/journal.ppat.1001187
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Global Gene Expression in Urine from Women with Urinary Tract Infection

Abstract: Murine models of urinary tract infection (UTI) have provided substantial data identifying uropathogenic E. coli (UPEC) virulence factors and assessing their expression in vivo. However, it is unclear how gene expression in these animal models compares to UPEC gene expression during UTI in humans. To address this, we used a UPEC strain CFT073-specific microarray to measure global gene expression in eight E. coli isolates monitored directly from the urine of eight women presenting at a clinic with bacteriuria. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
249
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 201 publications
(275 citation statements)
references
References 87 publications
(139 reference statements)
22
249
1
3
Order By: Relevance
“…A recent study evaluating UPEC gene expression in elderly men and women with UTI found yersiniabactin system genes to be expressed in only 13 of 21 UPEC cystitis isolates (45). In contrast, a microarray-based study evaluating UPEC gene expression from women at a hospital urology clinic found fyuA to be highly expressed in seven of eight UPEC cystitis isolates (46). Potential variability in UPEC yersiniabactin system gene expression between UTI patient subpopulations will likely need to be taken into account during UPEC vaccine design.…”
Section: Figmentioning
confidence: 96%
“…A recent study evaluating UPEC gene expression in elderly men and women with UTI found yersiniabactin system genes to be expressed in only 13 of 21 UPEC cystitis isolates (45). In contrast, a microarray-based study evaluating UPEC gene expression from women at a hospital urology clinic found fyuA to be highly expressed in seven of eight UPEC cystitis isolates (46). Potential variability in UPEC yersiniabactin system gene expression between UTI patient subpopulations will likely need to be taken into account during UPEC vaccine design.…”
Section: Figmentioning
confidence: 96%
“…This report highlights the untapped resource of bacteria-specific small molecules as potential vaccine antigens and provides a proof of principle for incorporating these compounds into multicomponent vaccines for the prevention of bacterial infections. transcriptomic, and proteomic studies that have also identified iron acquisition systems as prime anti-UTI targets (21)(22)(23)(24)(25)(26)(27).…”
Section: Significancementioning
confidence: 99%
“…Prominent among these is the Yersinia high pathogenicity island (HPI), which encodes the biosynthetic machinery to make the specialized metabolites yersiniabactin (Ybt) and escherichelin (2). Direct mass spectrometric detection of urinary Ybt in UTI patients, serological markers, transcriptional signatures, and experimental infection models all indicate active expression of Yersinia HPI proteins during UTI pathogenesis (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%